Research on Reverse Measuring Method of Screw Drill Rotor Based on Axis Section. Issue 1 (January 2020) - Li, Daqi; Wei, Xuetong; Yang, Lingyi; Song, Yujie; Bi, Dalong
Abstract: The screw drilling tool is an important underground power tool in the oil fields. During the working process, the rotor will be damaged or unevenly worn. The repair and reuse of the damaged area of the rotor will greatly improve the utilization rate of the screw drilling tool and reduce the mining cost. To this end, based on the formation principle of the rotor surface of the five-head screw drill, the curve coordinates are described by the ray length and the rotation angle. The axis relationship equation is characterized by exploring the intrinsic relationship between the two coordinates, and the reverse model of a single screw drill rotor was constructed by point collection. At the same time, the experimental research was carried out to verify the feasibility of modeling the screw drilling tool according to the axial section. In order to provide an effective way to reverse the entire body based on the unworn area of the screw drilling tool, the inverse modeling theory of the spiral surface entity is greatly enriched.